Occupational Health and Safety Issues Among Nurses in the Philippines - de Castro, A. B. (2009)
Nursing is a hazardous occupation in the United States, but little is known about workplace health and safety issues facing the nursing work force in the Philippines. In this article, work-related problems among a sample of nurses in the Philippines are described. Cross-sectional data were collected through a self-administered survey during the Philippine Nurses Association 2007 convention. Measures included four categories: work-related demographics, occupational injury/illness, reporting behavior, and safety concerns. Approximately 40% of nurses had experienced at least one injury or illness in the past year, and 80% had experienced back pain. Most who had an injury did not report it. The top ranking concerns were stress and overwork. Filipino nurses encounter considerable health and safety concerns that are similar to those encountered by nurses in other countries. Future research should examine the work organization factors that contribute to these concerns and strengthen policies to promote health and safety.